A large Turkish pedigree with multiple endocrine neoplasia type 1 syndrome carrying a rare mutation: c.1680_1683 del TGAG - Demirtaş, Coşkun Özer; Ata, Pınar; Çetin, Ali; Türkyılmaz, Ayberk; Guney Duman, Deniz (Turkish Journal of Gastroenterology, 2020)
Background & Aims: Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant syndrome characterized by tumors arising from endocrine glands with no specific genotype-phenotype correlation. Herein, we report the largest Turkish kindred with MEN1 inherited a scarce MEN1 mutation gene. Materials and Methods: Sixty-four year-old man, referred to our gastroenterology outpatient clinic for evaluation of pancreatic mass lesion, was diagnosed with MEN1-syndrome after endoscopic ultrasound guided sampling of the mass revealing pancreatic neuroendocrine tumor (pNET), and accompanying primary hyperparathyroidism (PHPT) and pituitary tumor. Genetic analysis by whole gene Sanger sequencing of MEN1 gene identified a frame-shift mutation in exon 10 (c.1680_1683delTGAG). All the relatives of the index case were proposed for clinical and genetic evaluation for MEN1-syndrome. Results: Of the 25 relatives of the index case, 17 were diagnosed MEN1-syndrome. Eighteen members among all relatives consented to genetic analysis and 11 had the same mutation as the index case. All the mutation positive members had MEN1, while none of mutation negative subjects had any sign of MEN1-syndrome. The frequencies of PHPT, pNET and pituitary tumors in this kindred were 94.1% (16/17), 29.4% (5/17) and 29.4% (5/17) respectively. Conclusion: We report rare MEN1 gene mutation which was descibed in a single sporadic patient before. It inherited in at least three generations of a large family, which has proven strong dominant effect on MEN1 phenotype. Further researches may be conducted to clarify potential candidacy of this mutation, as a hotspot for MEN1 patients, especially in Turkish population.